Developing HTML5-Based Interactive Media to Improve Writing Letter Capital Skills in Narrative Texts (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2026)
This research’s aims to develop HTML5-based interactive media to overcome students' writing skills problems for grade IV. This research uses the Research and Development method, Borg and Gall model which consists of observation, development, validation, trial and evaluation stages. Data analysis was done through validity, reliability, normality, wilcoxon, and N-gain tests. The media and material validity test results showed an average of 96.25%, which is a very feasible category. The results of the wilcoxon test show that Asymp. Sig (2-tailed) is worth 0.000 that "Ha is accepted". The N-gain test yielded 70.43% indicating that the medium was quite effective. The student and teacher responses questionnaire at the end of learning showed that the media was worthy for use in learning. This study implies that using HTML5-based interactive media effectively improves capital letter writing skills in students' narrative texts.